Business models of digital audio distribution - Hlaváček, Ondřej (2008)
This thesis considers current status of recording industry divided into two parts -- music and audiobooks, either in the whole world and Czech Republic. Used technologies, payment systems and business models are examined alongside with fresh information from recording industry. The models part describes an ideal business model, which incorporates current trends and creates a vision of the business in the future. Applied part adjusts this model according to real world factors into a model usable in the Czech Republic. A final SWOT analysis describes all strengths, weaknesses, opportunities and threats of the given model.